The Health Education Specialist Practice Analysis III 2025 (HESPA III 2025): Process and Outcomes - Antonio J. Gardner; Beth H. Chaney; Ian F. Hembry; James Henderson; Misozi Houston; William Datema; Cherylee Sherry; Shontelle Dixon; Melissa Opp (Health Education & Behavior, 2026)
The Health Education Specialist Practice Analysis III 2025 was conducted to update and validate the hierarchical model associated with the contemporary framework for the practice of health education specialists across work settings at entry and advanced levels. The purpose of this manuscript was to report the processes and findings associated with the HESPA III 2025 study to assess the validity of the Areas of Responsibility, Competencies, Sub-competencies, and Knowledge Areas for entry- and advanced-level health education specialists. Quantitative and qualitative methods were employed. Three data collection instruments were developed by the Health Education Specialist Practice Analysis III 2025 Steering Committee and a 14-member Practice Analysis Panel to survey practicing health education specialists on the knowledge and skills needed to perform duties in their ongoing roles. The instruments assessed the importance, frequency, and performance expectations of the elements of the model. Composite scores for Sub-Competencies were calculated, and subgroup comparisons were conducted to distinguish between levels of practice. A total of 2,337 health education specialists completed the surveys. The final validated hierarchical model included nine Areas of Responsibility, 35 Entry-level Competencies, 4 Advanced-level Competencies, 243 Sub-Competencies, nine Knowledge Topics, and 141 Knowledge Statements. Of the Sub-Competencies, 145 were classified as entry-level, and 98 were classified as advanced level. Health Education Specialist Practice Analysis III 2025 produced a validated hierarchical model descriptive of the current practice of health education specialists across work settings. The findings have professional preparation, professional development, and certification implications for the health education profession.